A note on arewise connected sets and functions - Yadav S.R.; Mukherjee R.N. (My University, 2025)
We introduce a new class of generalized arcwise connected functions and discuss their basic properties. Our generalization is illustrated by an example and an application is given for a mathematical programming problem involving this new class of functions. © 1985, Australian Mathematical Society. All rights reserved.